41 Clinical Utility of Ultrasensitive ctDNA Detection Across the Renal Cell Carcinoma Disease Spectrum: A Multi-Cohort Retrospective Study - Ezra Blumenthal; Paulo Siqueira do Amaral; Yi Chen; Charles Abbott; Richard Chen; Kelvin Moses; Kerry Schaffer; Scott Haake; Brian Rini; Alan Tan (The Oncologist, 2026)
Abstract Background Circulating tumor DNA (ctDNA) is an emerging tool for non-invasive disease monitoring in solid tumor oncology, yet its clinical utility in renal cell carcinoma (RCC) remains poorly defined. RCC exhibits variable ctDNA shedding rates, which may limit assay sensitivity particularly in low-burden disease states, and prospective data evaluating ctDNA across the RCC disease spectrum are limited. Ultrasensitive ctDNA detection may offer a valuable tool for perioperative risk stratification, minimal residual disease assessment in the post-surgical setting, and real-time treatment monitoring in metastatic disease. Methods We conducted a single-center retrospective cohort study of patients with RCC who underwent ctDNA testing using the NeXT Personal Dx® assay, an ultrasensitive tumor-informed platform that uses patient-specific variants identified by whole-genome sequencing, with a detection threshold of ∼1 part per million (ppm). Patients were stratified into three cohorts based on disease setting at the time of initial ctDNA measurement: perioperative (ctDNA-positive prior to nephrectomy), adjuvant/surveillance (post-nephrectomy monitoring without a pre-nephrectomy ctDNA measurement), and metastatic (ctDNA-positive patients with known metastatic disease initiating a new line of systemic therapy). Primary endpoints included ctDNA detectability, longitudinal ctDNA kinetics, and concordance with radiographic disease assessment. Associations between histologic features and ctDNA status were evaluated by Fisher’s exact test; ctDNA kinetics in the metastatic cohort were assessed by Mann-Whitney U test. Results Fifty-seven unique patients were included across 60 cohort entries; three patients appeared in both the adjuvant/surveillance and metastatic cohorts, reflecting progression during surveillance and subsequent initiation of systemic therapy. Seventy-nine percent had clear cell RCC. The perioperative cohort (n = 3) had ctDNA detectable prior to nephrectomy (median 35 ppm, range 19–208); all achieved ctDNA clearance post-surgery. In the adjuvant/surveillance cohort (n = 25), ctDNA was detectable at any timepoint in 8 patients (32%) at a median follow-up of 12.2 months (range 4.3–20.9). ctDNA positivity was significantly associated with sarcomatoid/rhabdoid differentiation (75% vs. 18%, p = 0.010), tumor necrosis (88% vs. 29%, p = 0.011), and WHO/ISUP grade 4 histology (75% vs. 18%, p = 0.010). Five patients (20%) developed radiographic progression at a median of 12.4 months (range 5.4–13.5); all were ctDNA-positive. Among the 3 ctDNA-positive patients who did not progress, median follow-up was 11.6 months (range 4.7–11.9). Zero of 17 ctDNA-negative patients progressed (100% NPV). Among the 18 patients with consistently undetectable ctDNA during the first 9 months post-nephrectomy, none progressed at a median follow-up of 11.7 months (range 4.3–20.1), including one patient who subsequently developed low-level ctDNA positivity beyond the 9-month window. The metastatic cohort comprised 32/32 ctDNA-positive patients (100% PPV); of these, 15 had paired baseline and 3-month assessments available for ctDNA kinetics analysis (median baseline ctDNA 175 ppm, range 18–7,935). Treatments in the kinetics subcohort included IO (n = 7), TKI (n = 5), IO/TKI (n = 2), and HIF-2α inhibitor (n = 1). Seven patients (47%) experienced radiographic progression at a median follow-up of 3.5 months (range 2.8–4.4). Early ctDNA kinetics demonstrated strong concordance with imaging outcomes (13/15, 87%): all 7 progressors showed rising ctDNA (median Log2 fold change +2.67), while 6 of 8 non-progressors showed ctDNA decline (median Log2 fold change −2.21; Mann-Whitney U p = 0.0012). Using any ctDNA rise as a threshold yielded 100% sensitivity and 100% NPV for radiographic progression. Baseline ctDNA level did not associate with subsequent progression (p = 0.77). Conclusions In this multi-cohort RCC study, ultrasensitive ctDNA detection demonstrated clinical utility across the disease spectrum, supporting its prospective evaluation as a tool for risk stratification and response assessment.